Lysine supplementation of barley wet distillers' solids diets for growing-finishing pigs - Valaja, Jarmo; Siljander-Rasi, Hilkka; Alaviuhkola, Timo; Rantanen, Asko (Agricultural Research Centre of Finland, 1996)
A growth experiment was conducted to study the effect of different lysine supplementation levels of barley wet distillers' solids (WDS) diets on the performance and the carcass quality of pigs (25.5-95.5 kg live weight). A total of 160 pigs were divided into four groups of 40 animals. Four pigs of the same sex were placed in each pen and fed one of the four experimental diets: a barley-soyabean meal (SBM) control diet (167 g crude protein (CP) /kg dry matter (DM) and 7.6 g lysine/feed unit (FU)) or three similar barley-WDS diets (204 g CP/kg DM) which were supplemented with synthetic lysine to contain 7.7, 9.2 or 10.7 g lysine/FU. Lysine supplementation linearly improved the daily weight gain (DG) and feed conversion ratio (FCR) of the pigs during growing (1-5 weeks) (p < 0.00 1), finishing (6th week onward) (p < 0.001) and the whole experimental period (p < 0.001). However, during the whole growing-finishing period the performance of the pigs levelled off at the lysine level of 9.2 g/FU and daily supply of 18.0 g, respectively(quadratic effect: p < 0.05 for DG and p < 0.01 for FCR). The pigs on the SBM diet grew faster and more efficiently than did the pigs on the WDS diets with similar lysine content (p < 0.05).
Keywords: Ko; lihasika; sika; aminohapot; lysiini; rankki; tärkkelysteollisuus; oheistuote; kasvu; rehumuutossuhde; teuraslaatu; rehut; ruokinta; swine; daily weight gain; feed conversion efficiency; amino acids; soyabean meal